2015
DOI: 10.3347/kjp.2015.53.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Toxoplasma gondii</i> in Dogs in Zhanjiang, Southern China

Abstract: Toxoplasmosis, caused by Toxoplasma gondii, is a parasitic zoonosis with worldwide distribution. The present study investigated the prevalence of T. gondii in dogs in Zhanjiang city, southern China, using both serological and molecular detection. A total of 364 serum samples and 432 liver tissue samples were collected from the slaughter house between December 2012 and January 2013 and were examined for T. gondii IgG antibody by ELISA and T. gondii DNA by semi-nested PCR based on B1 gene, respectively. The over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It may cause asymptomatic infection or severe symptomatic infection including developmental defects, early embryonic death, stillbirth, or abortion to T. gondii-infected pregnancies (Dubey and Jones, 2008;Dubey and Dubey, 2010;Pan et al, 2017). Dogs are the intermediate hosts, and multiple studies have demonstrated the prevalence of T. gondii in dogs in a variety of countries or areas worldwide (Jiang et al, 2015;Zhang et al, 2015;Dubey et al, 2016;Rengifo-Herrera et al, 2017;Zarra-Nezhad et al, 2017). Although these serological surveys and diagnosis analysis of dogs infected T. gondii have been reported, the interactions between the host dog and the parasite T. gondii remain not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…It may cause asymptomatic infection or severe symptomatic infection including developmental defects, early embryonic death, stillbirth, or abortion to T. gondii-infected pregnancies (Dubey and Jones, 2008;Dubey and Dubey, 2010;Pan et al, 2017). Dogs are the intermediate hosts, and multiple studies have demonstrated the prevalence of T. gondii in dogs in a variety of countries or areas worldwide (Jiang et al, 2015;Zhang et al, 2015;Dubey et al, 2016;Rengifo-Herrera et al, 2017;Zarra-Nezhad et al, 2017). Although these serological surveys and diagnosis analysis of dogs infected T. gondii have been reported, the interactions between the host dog and the parasite T. gondii remain not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these countries of highly antigen prevalence might be contaminated with Toxoplasma gondii in the environment, and then the warm-blood mammals including humans could be infected more easily by environmental and food contaminated T. gondii. In China, which showed high antigen-positive rates in cats, the rate of dog antigens was also relatively high, ranging from 3.7% to 8.6% [9,14]. In this study, antigen prevalence of T. gondii of domestic and stray dogs and cats in South Korea was very low as much as that of Japan.…”
Section: B Amentioning
confidence: 48%
“…The seroprevalence of stray dogs in Japan was lower than that of Korea [8], and consequently the environmental contamination of T. gondii is likely lower in Japan than in Korea. The seroprevalence of T. gondii in dogs in China ranged from 21% to 51.9% and 69.8% in Brazil [9,14,31,32]. Therefore, the environmental toxoplasma contamination of these countries as well as the rate of cat toxoplasmosis infection, is expected to be very high.…”
Section: B Amentioning
confidence: 99%
See 2 more Smart Citations